Individualized Rating Scales of Engagement during Group Exercise Activities for Children with Multiple and Severe Disabilities: A Process Description and Case Series - Kendall, Eydie; Streagle, Karren; Helbert, Tania (Journal of the American Academy of Special Education Professionals, 2022)
Engagement is important for learning. Because of their atypical expression, measuring engagement for students with multiple and severe disabilities (MSD) is challenging. Group activities often enhance engagement of children and gross motor activities include an expanded variety of behaviors by which engagement may be measured. The purpose of this Manuscript is to outline a process for developing and implementing individualized rating scales to measure the engagement of students with MSD participating in a group exercise program. A series of three cases demonstrates the process and illustrates how the results might benefit a child with MSD.